2019
DOI: 10.3788/col201917.111603
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable continuous-zoom metalens in visible band

Abstract: Design of a conventional zoom lens is always challengeable because it requires not only sophisticated optical design strategy, but also complex and precise mechanical structures for lens adjustment. In this paper, we propose a continuous zoom lens consisting of two chiral geometric metasurfaces with dielectric nanobrick arrays sitting on a transparent substrate. The metalens can continuously vary the focal length by rotating either of the two metasurfaces along its optical axis without changing any other condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 38 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…[147,148] A derivative of the Alvarez system is also presented where the two lenses are coaxially rotated rather than being parallelly moved, which is inspired by the Moiré lens. [149][150][151][152][153] Cui et al [151] proposed a rotationally tunable polarization-dependent varifocal metasurface, and Yilmaz et al [152] demonstrated a polarizationindependent varifocal metasurface. Subsequently, Guo et al [153] fabricated a 3.5× continuous varifocal meta-lens in the microwave band, with an improved N.A.…”
Section: External Tunabilitymentioning
confidence: 99%
“…[147,148] A derivative of the Alvarez system is also presented where the two lenses are coaxially rotated rather than being parallelly moved, which is inspired by the Moiré lens. [149][150][151][152][153] Cui et al [151] proposed a rotationally tunable polarization-dependent varifocal metasurface, and Yilmaz et al [152] demonstrated a polarizationindependent varifocal metasurface. Subsequently, Guo et al [153] fabricated a 3.5× continuous varifocal meta-lens in the microwave band, with an improved N.A.…”
Section: External Tunabilitymentioning
confidence: 99%
“…This kind of step-zoom metalens can readily switch between two FOVs and has potential application in target tracking and recognition. In 2019, Cui et al combined the Moire effect with GEMS, and by rotating one of the two GEMS, the focal length changes from −∞ to +∞ theoretically ( Figure 10C) [85]. [79].…”
Section: Multifunction and Information Multiplexing 531 Multifunctimentioning
confidence: 99%
“…(C) Continuous-zoom metalens conducted with Moire effect[85]. Reprint permission obtained from[83][84][85].above work, Wang et al designed two different nanostructures to manipulate the phase of RCP and LCP light independently (Figure 11H)[93] rather than the opposite phase control of two CP light with different handedness. This kind of CP-selective metasurface can reduce the interference of light with different handedness to the diffraction results.…”
mentioning
confidence: 99%
“…Tunable focal length, or varifocal lens, is one of the most probable and expected functionalities of metalens. A number of mechanical tuning techniques have been developed such as stretching the metalens on the elastic substrate [21][22][23], MEMs-actuated silicon metasurface lens [24], MEMsactuated axially moving metasurface doublet lens [25], manually-actuated [26][27] or MEMs-actuated [1] laterally moving two cubic phase metasurfaces of an Alvarez lens, and controlling the angular orientation of the metalens doublets [28][29][30]. Furthermore, other forms of tuning such as incorporating tunable materials into metasurfaces for changing focal position have been studied [20,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%